The new law for the right to housing in Spain in the European context: Strengths and weaknesses - Argelich Comelles, Cristina (2023)
This document analyses the main developments introduced by the Law on the Right to Housing, approved in Spain. This concerns mainly tenancy rent control, as well as consumer, urban planning, and administrative measures.This legal analysis is framed within the framework of measures of access to housing in European comparative law, to verify the existence of other viable remedies, some of them raised in the Spain 2050 Report and not regulated.